2021
DOI: 10.1111/1475-6773.13633
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of black and white hysterectomy incidence among reproductive aged women

Abstract: Objective To investigate the intersection of race and economic context in treatment with hysterectomy among reproductive aged women with noncancerous gynecologic conditions. Data Sources We combined administrative billing records of inpatient and outpatient hysterectomy procedures (N = 28 301) occurring in North Carolina between 2011 and 2014 with census data to calculate county‐level hysterectomy rates. Study Design Spatial analysis techniques examined the distribution of black and white hysterectomy rates ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Age at the time of the final [12,[40][41][42][43][44] and were all associated with an earlier age at FMP [34,45]. The occurrence of ovarian and uterine surgery prior to natural menopause is an impediment to determining the age at which FMP occurs; germane to this review, Black-White differences exist in the experience of these surgeries [46,47]. In the cross-sectional survey Black women were twice as likely as White women to have undergone hysterectomy/oophorectomy (30% vs 15%) [48], with Black women's elevated risk continuing throughout cohort follow-up [49].…”
Section: Age At Which the Final Menstrual Period Occursmentioning
confidence: 99%
“…Age at the time of the final [12,[40][41][42][43][44] and were all associated with an earlier age at FMP [34,45]. The occurrence of ovarian and uterine surgery prior to natural menopause is an impediment to determining the age at which FMP occurs; germane to this review, Black-White differences exist in the experience of these surgeries [46,47]. In the cross-sectional survey Black women were twice as likely as White women to have undergone hysterectomy/oophorectomy (30% vs 15%) [48], with Black women's elevated risk continuing throughout cohort follow-up [49].…”
Section: Age At Which the Final Menstrual Period Occursmentioning
confidence: 99%
“…(Obstet Gynecol 2023;142:350-9) DOI: 10.1097/AOG.0000000000005225 R ates of hysterectomy before menopause remain disproportionately high among U.S. Black populations and in U.S. territories such as Puerto Rico. [1][2][3][4][5][6] Hysterectomy, an effective treatment for gynecologic conditions such as uterine leiomyomas (fibroids) and dysmenorrhea, 7 is also sterilizing. Overtreatment with sterilizing procedures remains a concern among marginalized communities, given state-sponsored eugenics programs in the 20 th century and the even longer history of gynecologic abuse of Black women.…”
Section: Discussionmentioning
confidence: 99%
“…We scored each patient on severity of their gynecologic symptoms on three domains: bulk, vaginal bleeding, and pelvic pain. [2][3][4][5][6] The construction and validation of the severity scores are described in detail elsewhere. 20 Our dichotomous outcomes were Yes/No to being in the top 25 th percentile of bulk, pelvic pain, or bleeding symptom severity scores.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Vincent et al (2021) demonstrated in their qualitative study that socioeconomic status is still one of the most important factors affecting women's reproductive health in Nigeria, where the process of reducing maternal and child mortality is slow and factors such as age, education, material and human capital, economic-nancial inequality, and men's participation in reproductive health activities were deemed effective in the reproductive health of women [17]. Gartner et al (2021) discovered that the rate of hysterectomy was higher in areas with higher socioeconomic levels, the main cause of which is unknown, but may be due to the higher proportion of blacks in these cities than whites Stable employment and a steady income are two bene ts that can ease a woman's menopause by reducing nancial stress [21]. Poor socioeconomic status, in general, is related to poor health outcomes in women of all ages [22].…”
Section: Discussionmentioning
confidence: 99%